Blockchain e Inteligencia Artificial: Una alternativa para un pago justo a los titulares de los derechos de autor - Córdova Balda, Pedro (2025)
Collective management societies emerged to help copyright holders receive fair compensation for the exploitation of their works. However, technological and logistical limitations have facilitated abuses that still persist. Globally, these entities have deviated from their purpose, restricting the proper use of works and facing accusations of monopoly and market abuse. As a solution, blockchain enables traceability and monitoring of works, especially in visual arts. When integrated with platforms and AI, it could facilitate royalty collection with lower administrative costs, preventing abuses and ensuring that those who exploit a work pay directly to the copyright holders.